2012
DOI: 10.1021/ic301219z
|View full text |Cite
|
Sign up to set email alerts
|

Pteridine Cleavage Facilitates DNA Photocleavage by Ru(II) Polypyridyl Compounds

Abstract: The synthesis, characterization, binding to calf thymus DNA, and plasmid DNA photocleavage studies of two ruthenium(II) pteridinylphenanthroline complexes are reported where the new pteridinylphenantholine ligands in these complexes are additions to a larger family designed to resemble DNA bases. [Ru(bpy)(2)(L-keto)](PF(6))(2)1 is synthesized from ligand substitution of Ru(bpy)(2)Cl(2) by 4-keto-pteridino[6,7-f]phenanthroline (L-keto). Increasing the reaction temperature during synthesis of 1 causes a ring sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 59 publications
0
11
0
2
Order By: Relevance
“…The reason for this was probably due to the introduction of ‘relaxed’ metal into the porphyrin to stimulate the triplet state, which prevented the bimolecular quenching by oxygen . However, Por 2 could also produce 1 O 2 to a smaller extent, which may be attributed to the hydrophilic part of the Ru–phenanthroline complex, as some types of Ru complex also have a certain photodynamic activity …”
Section: Resultsmentioning
confidence: 99%
“…The reason for this was probably due to the introduction of ‘relaxed’ metal into the porphyrin to stimulate the triplet state, which prevented the bimolecular quenching by oxygen . However, Por 2 could also produce 1 O 2 to a smaller extent, which may be attributed to the hydrophilic part of the Ru–phenanthroline complex, as some types of Ru complex also have a certain photodynamic activity …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, complexes 1 cleave DNA by the quite active singlet oxygen [27,28] and mainly performs a singlet oxygen photosensitization mechanism. Under light irradiation, Ru(II) polypyridyl complexes are easily excited and undergo an intramolecular electron transfer, and thus the excited-state complexes can rapidly react with oxygen molecules around to produce the quite active singlet oxygen.…”
Section: Dna-photocleavage Abilities and Mechanism Of Chiral Complexesmentioning
confidence: 99%
“…In a different study, complexes [Ru(bpy) 2 (L-keto)] 2+ and [Ru(bpy) 2 (L-aap)] 2+ have been shown to be good intercalators of CT-DNA. 40 The latter exhibits an unusually high ability to photocleave pBR322 plasmid under aerobic conditions. This was suppressed upon addition of azide -a singlet oxygen scavenger -or when the reaction was carried out under anaerobic conditions.…”
Section: Non-covalent Interactions Of Metal Complexes With Dnamentioning
confidence: 99%